Acute physical exercise and hypertension in the elderly: A systematic review - Reia, Thaís Amanda [UNESP]; da Silva, Roberta Fernanda [UNESP]; Jacomini, André Mourão [UNESP]; Moreno, Ana Maria Guilmo; da Silva, Anderson Bernardino [UNESP]; Monteiro, Henrique Luiz [UNESP]; Zago, Anderson Saranz [UNESP] (My University, 2020)
As the population ages, health conditions, including hypertension (HT), which is one of the most prevalent diseases in the elderly population, increase. Regular physical exercise has been recommended for hypertensive individuals; however, due to the variety of factors involved in exercise, different acute responses can be achie-ved. Accordingly, the purpose of this study was to perform a systematic review of the acute effect of physical exercise on blood pressure (BP) in elderly hypertensive patients and of its applicability to the treatment of HT. The search was performed in electronic databases available at Pubmed/Medline, Scopus and Bireme from 2008 to 2018, using the terms “acute physical exercise and hypertension and elderly”. A total of 592 articles were found, and after applying the inclusion criteria, 9 articles were selected to form the analysis. All studies evaluated the acute effect of the exercise session and the acute effect of the session after a training period in male and female hypertensive individuals aged 60 years or over. The results indicate that in spite of the heterogeneity of training methods, all intervention protocols used in these studies were effective in promoting BP reduction post exercise when compared to the control group. However, there is still a gap in the reviewed literature regarding the maintenance time of post exercise hypotension (PEH) in the elderly. This information could suggest how long individuals undergoing physical exercise would be “protected” from high blood pressure values and their health risks, and help plan physical exercise sessions at the precise time the hypotensive effect ceases to be present. Level of evidence II; Therapeutic studies-Investigation of treatment results.
Ejercicio físico agudo e hipertensión arterial en ancianos: Revisión sistemática
Exercício físico agudo e hipertensão arterial em idosos: Revisão sistemática
Keywords: Aging; Arterial hypertension; Physical exercise; Post-exercise hypotension